2009
DOI: 10.1080/00102200802483498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Particle Size Measurements with Laser-Induced Incandescence, Mass Spectroscopy, and Scanning Mobility Particle Sizing in a Laminar Premixed Ethylene/Air Flame

Abstract: Particle size distribution functions (PSDF) and mean particle sizes have been determined in a laminar premixed ethylene/air flame with three different experimental approaches: photo-ionization mass spectrometry (PIMS), scanning mobility particle sizing (SMPS), and laser-induced incandescence (LII). The main goal of this investigation was the crossvalidation of these three methods used at our institute for the determination of particle sizes in a great variety of flames or exhaust gases. We found good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…This method has been used to measure laboratory generated BC particles smaller than 7 nm. 26 Similarly, the principle of operation of the SP2 and its use in ambient sampling have been described extensively. 19,27−29 Individual BC particles sampled by the SP2 were irradiated with a continuous laser (1064 nm) resulting in BC incandescence whichwasmonitoredinthevisibleband(λ = 300−550 nm).…”
Section: Methodsmentioning
confidence: 99%
“…This method has been used to measure laboratory generated BC particles smaller than 7 nm. 26 Similarly, the principle of operation of the SP2 and its use in ambient sampling have been described extensively. 19,27−29 Individual BC particles sampled by the SP2 were irradiated with a continuous laser (1064 nm) resulting in BC incandescence whichwasmonitoredinthevisibleband(λ = 300−550 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies in the literature have made inter-comparisons of soot particle size measurement in flat premixed flames using different techniques for the purpose of either understanding the advantages and disadvantages of photoionization mass spectrometry (PIMS), SMPS, and LII and their applicability range (Stirn et al 2009) or investigating the causes for the different soot particle sizes measured by SMPS and TEM ). However, there have been no studies to demonstrate the potential of using LII to measure the size of incipient soot in nucleation flames.…”
Section: Comparison Of Size Distributions Of Incipient Soot By Lii-himentioning
confidence: 99%
“…Finally, it is worth pointing out that the goal of this study is to explore the potential of using LII as an in situ sizing technique for incipient soot particles in the nucleation region of flames where the particle size distribution is unimodal. It has been well-established that the size distribution function of particle mobility diameter evolves into a bimodal distribution above the nucleation zone in sooting flames due to the presence of both particle nucleation and aggregation (Zhao et al 2003Abid et al 2008;Stirn et al 2009). Under these conditions, it is not feasible to use LII to retrieve the bimodality of the particle size distribution since small particles contribute negligibly to the LII signals in the presence of large ones.…”
Section: Comparison Of Size Distributions Of Incipient Soot By Lii-himentioning
confidence: 99%
See 1 more Smart Citation
“…Although inflame soot size distributions are sometimes bimodal (Stirn et al, 2009), a numerical analysis performed by Johnsson et al (2010) showed that the TiRe-LII signal was insensitive to the smaller-size mode. The following widely used assumption for the inflame soot particle size distribution is adopted here:…”
Section: Determination Of Particle Size Distributionmentioning
confidence: 99%